Organizational Dehumanization Impact on Knowledge Hiding and Employee Theft Time: Moderating Effect of Psychological Capital (Journal of Asian Development Studies, 2024)
This study illustrates when organizational dehumanization leads to infrequent (deviant) job behavior. So, this study aims to investigate the impact of organizational dehumanization on perceived incivility, knowledge hiding, and employee theft time. In addition, the moderating effect of psychological capital is examined among organizational dehumanization and perceived incivility, as well as the mediation of perceived incivility about organizational dehumanization and deviant (abnormal) job behavior (time theft and knowledge hiding). This study is based on the COR and SET theory. The information was gathered from manufacturing sector employees utilizing the time-lag method of intervals T1/T2/T3 correspondingly. The data demonstrate that organizational dissent is a problem. Additionally, the psychological capital of the workforce reduced the negative impacts of organizational dehumanization on perceived rudeness. This study offers insights into reducing organizational stressors to buffer employee deviant behaviors by considering behavioral results of organizational dehumanization or management. This study also provides directions for new manufacturing industry research